2000
DOI: 10.1002/1097-4644(20000901)78:3<442::aid-jcb9>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Major DNA replication initiation sites in thec-myc locus in human cells

Abstract: DNA replication initiation sites and initiation frequencies over 12. 5 kb of the human c-myc locus, including 4.6 kb of new 5' sequence, were determined based on short nascent DNA abundance measured by competitive polymerase chain reaction using 21 primer sets. In previous measurements, no comparative quantitation of nascent strand abundance was performed, and distinction of major from minor initiation sites was not feasible. Two major initiation sites were identified in this study. One predominant site has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 51 publications
10
85
0
Order By: Relevance
“…To distinguish between these two possibilities, we analyzed the activities of two well-characterized replication origins, namely the lamin B2 (Giacca et al, 1994; Abdurashidova et al, 2000) and cmyc (Tao et al, 2000) (Fig. 3A), by measuring the nascent-strand abundance at these chromosomal regions, as previously described (Giacca et al, 1997;Tao et al, 2000).…”
Section: Journal Of Cell Science 592mentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish between these two possibilities, we analyzed the activities of two well-characterized replication origins, namely the lamin B2 (Giacca et al, 1994; Abdurashidova et al, 2000) and cmyc (Tao et al, 2000) (Fig. 3A), by measuring the nascent-strand abundance at these chromosomal regions, as previously described (Giacca et al, 1997;Tao et al, 2000).…”
Section: Journal Of Cell Science 592mentioning
confidence: 99%
“…Isolation of genomic and nascent-strand DNA Isolation of nascent-strand DNA was performed using the exonuclease method as previously described (Giacca et al, 1997;Tao et al, 2000). Briefly, the cells were washed twice with PBS and lysed in Hirt's lysis buffer (50 mM Tris-HCl, pH 8.0, 0.6 M NaCl, 1 mM EDTA and 0.5% SDS) (Hirt, 1967).…”
Section: Journal Of Cell Science 121 (5)mentioning
confidence: 99%
“…PCR Analysis for Nascent Strand Abundance DNA replication initiation frequencies at the human c-Myc and ß-globin locus were determined based on short nascent DNA abundance (Aladjem et al, 1998;Kamath and Leffak, 2001;Malott and Leffak, 1999;Tao et al, 2000). The 1-2 kb fraction of nascent DNA was Isolated by alkaline gel lysis of cells In logarithmic growth and quantitated by slot blot hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the initiation activity at chromosomal sites, the abundance of short nascent DNA strands was quantitated by PCR at two loci containing known origins of DNA replication, c-myc and ß-globin ( Figure 4). In both of these regions, the abundance and size distribution of DNA nascent strands suggests that there are multiple, nonrandom sites of replication initiation (Kamath and Leffak, 2001;Malott and Leffak, 1999;Tao et al, 2000). The pattern of nascent strand abundance at these specific initiation sites was unchanged between +/+ and A/-cells, suggesting that at least for these two origins, replication initiated normally in the A/-cells that do enter S phase.…”
Section: Replication From Orip Of Epstein-barr Virusmentioning
confidence: 99%
“…Extensive mapping of replication start sites in mammalian chromosomes has revealed that replication at most, but not all, loci begins at a few high frequency start sites contained within a broad zone of initiation (83,63,82,37,4,59, and other studies reviewed in 40,24,12). One of the most thoroughly mapped high frequency initiation Altaian, A.L.…”
Section: Introductionmentioning
confidence: 99%